Considerations regarding the post-modern context- conceptual issues - Pechula, Marcia Reami [UNESP] (Univ Federal Ceara, Programa Pos-graduacao & Filosofia, 2015)
This paper aims to expose reflections on the causes that generated both the dampening of seeking understanding the historical context in which we find ourselves and the claim of the speeches directed to sectors that have a more urgent need of acting and social solution. The attempt is to investigate if the weakening of seeking understanding the existence, or not, of a postmodernity is caused by the migration of a general concern for the interests of local scope (pragmatist). The theme is justified, in our view, on the academic speech that, at the same time, it preaches a multidisciplinary, interdisciplinary, transdisciplinary and multiculturalist action, it maintains a condition increasingly fragmented, forging ghettos or communities (using a web expression) arranged from ever greater restricted interests, promoting a detachment of macro social interests.
Keywords: Modernity; Postmodernity; Speech; Philosophy